Line of duty. Series 2 [videorecording (DVD)] - Compston, Martin; McClure, Vicky, 1983-; Dunbar, Adrian, 1958- (Acorn, 2013)
Season two has Lindsay Denton a member of AC12, a police anti-corruption unit, charged with investigating an ambush of a police convoy.